The vegetarian cookbook - Love, Carrie (DK Publishing, 2019)
Provides children with an illustrated cookbook containing more than fifty step-by-step recipes for breakfast foods, snacks, lunches, beverages, entrees, and desserts. Includes dozens of color photographs, information on kitchen safety and equipment, nutritional information, and a glossary.